AGAINST THE BACKGROUND OF ALLERGIC RHINITIS IN THE PATHOGENESIS OF SINUSITIS DEVELOPMENT - Касимов К.; Нарбаев З. К.; Рустамов А. (Web of Journals Publishing, 2023)
Relevance of the study. Acute sinusitis is one of the most common diseases among children, the largest number of patients is between the ages of 4 and 15 years, and over the past 10 years, the disease accounted for 35-37% of all diseases of the upper respiratory tract (1,2,4,5,7) Currently, the rate of acute and chronic rhinosinusitis is kept high, as the prevention of them and their complications is not fully developed. The occurrence and course of acute sinusitis is significantly influenced by various endogenous and exogenous factors, such as allergens, environmental irritants, and it can also have infectious, viral, bacterial or fungal etiology.